Survival and Flight Characteristics of Captive-Reared and Wild Northern Bobwhites in Texas - Robert M. Perez; Don E. Wilson; Karen D. Gruen (National Quail Symposium Proceedings, 2017)
Introductions of captive-reared northern bobwhite (Colinus virginianus) to bolster native populations have been largely unsuccessful. We compared the survival and flight characteristics of game-farm (n 46), first-generation (F1) (n = 48), wild translocated (n = 45), and wild native (n = 50) northern bobwhites. In November 1993, all birds were radio-collared, leg banded, sexed, and aged. Birds were then released on a study area in Brooks County, Texas in groups of about 15, 1 bird at a time. Upon release, the direction of departure, speed, and time required to reach cover were recorded. The mean flight speed and distance flown for wild bobwhites was significantly greater (P < 0.01) than captive-reared bobwhites. Wild native, wild translocated, and F1 groups were non-randomly distributed in direction of departure at release site (P < 0.01). Survival of wild groups was significantly higher than captive-raised groups (P < 0.05). The major cause of mortality in all groups was mammalian depredation. Fifteen F1 quail and 1 game-farm quail integrated into wild coveys. Our results re-confirm the inability of game-farm and first-generation northern bobwhites to survive in the wild, and we offer flight speed as one potential causal factor.
Keywords: Colinus virginianus; direction of departure; first generation; flight speed; northern bobwhite; south Texas; survival